Предмет: Математика,
автор: filkyza3
Решите уравнение 2 13 - 3 56 * ( 2 - 3х ) = 8 59 + 4 712 * ( - 1 13 + 2х )
Ответы
Автор ответа:
0
2 13-3 56*(2-3х)=8 59+4 712*(-1 13+2х)
2 1/3-3 5/6*2+3 5/6*3х=8 5/9-4 7/12*1 1/3+4 7/12*2х
2 1/3-23/6*2+23/6*3х=8 5/9-55/12*4/3+55/12*2х
2 1/3-23/3+23/2*х=8 5/9-55/9+55/6*х
2 1/3-7 2/3+11 1/2*х=8 5/9-6 1/9+9 1/6*х
11 1/2*х-5 1/3=9 1/6*х+2 4/9
11 1/2*х-9 1/6*х=2 4/9+5 1/3
11 3/6*х-9 1/6*х=2 4/9+5 3/9
2 2/6*х=7 7/9
2 1/3*х=7 7/9
х=7 7/9:2 1/3
х=70/9:7/3
х=70/9*3/7
х=10/3
х=3 1/3
Проверка:
2 1/3-3 5/6*(2-3*3 1/3)=8 5/9+4 7/12*(-1 1/3+2 *3 1/3)
2 1/3-23/6*(2-3*10/3)=8 5/9+4 7/12*(-1 1/3+2*10/3)
2 1/3-23/6*(2-10)=8 5/9+4 7/12*(-1 1/3+20/3)
2 1/3-23/6*(-8)=8 5/9+4 7/12*(-1 1/3+6 2/3)
2 1/3+23/3*4=8 5/9+55/12*5 1/3
2 1/3+92/3=8 5/9+55/12*16/3
2 1/3+30 2/3=8 5/9+55/3*4/3
32 3/3=8 5/9+220/9
33=8 5/9+24 4/9
33=32 9/9
33=33
2 1/3-3 5/6*2+3 5/6*3х=8 5/9-4 7/12*1 1/3+4 7/12*2х
2 1/3-23/6*2+23/6*3х=8 5/9-55/12*4/3+55/12*2х
2 1/3-23/3+23/2*х=8 5/9-55/9+55/6*х
2 1/3-7 2/3+11 1/2*х=8 5/9-6 1/9+9 1/6*х
11 1/2*х-5 1/3=9 1/6*х+2 4/9
11 1/2*х-9 1/6*х=2 4/9+5 1/3
11 3/6*х-9 1/6*х=2 4/9+5 3/9
2 2/6*х=7 7/9
2 1/3*х=7 7/9
х=7 7/9:2 1/3
х=70/9:7/3
х=70/9*3/7
х=10/3
х=3 1/3
Проверка:
2 1/3-3 5/6*(2-3*3 1/3)=8 5/9+4 7/12*(-1 1/3+2 *3 1/3)
2 1/3-23/6*(2-3*10/3)=8 5/9+4 7/12*(-1 1/3+2*10/3)
2 1/3-23/6*(2-10)=8 5/9+4 7/12*(-1 1/3+20/3)
2 1/3-23/6*(-8)=8 5/9+4 7/12*(-1 1/3+6 2/3)
2 1/3+23/3*4=8 5/9+55/12*5 1/3
2 1/3+92/3=8 5/9+55/12*16/3
2 1/3+30 2/3=8 5/9+55/3*4/3
32 3/3=8 5/9+220/9
33=8 5/9+24 4/9
33=32 9/9
33=33
Похожие вопросы
Предмет: Математика,
автор: lianak76
Предмет: Алгебра,
автор: banana738
Предмет: Алгебра,
автор: Oleg1717
Предмет: Математика,
автор: ponochkazu
Предмет: Геометрия,
автор: Bitaman